PENENTUAN NILAI PREMI ASURANSI PERTANIAN BERBASIS INDEKS CURAH HUJAN PADA KOMODITAS KEDELAI YANG DISIMULASI MENGGUNAKAN DISTRIBUSI WEIBULL - DEWI, NI PUTU AYUNDA SURYA; DHARMAWAN, KOMANG; SARI, KARTIKA (E-Jurnal Matematika; Vol 9 No 4 (2020), 2020)
Agricultural insurance protects farmers who experience crop failure. This study aims to calculat e the value of agricultural insurance premium by applying simulated rainfall index-based using stochastic weather generator on soybean commodities in Negara sub-district . This study are used rainfall data to determine the probability of the transition, then perform rainfall simulations using the Stochastic Weather Generator method to obtain trigger values and continued with the calculation of agricultural insurance premiums. Results of this study provide the value that higher trigger is taken, the greater the insurance premium that must be paid. The value of insurance premiums to be paid is 4,18% - 5,66% of insurance costs Rp2.605.000,00.